Depth wide distribution and metabolic potential of chemolithoautotrophic microorganisms reactivated from deep continental granitic crust underneath the Deccan Traps at Koyna, India - Mandal, Sunanda; Bose, Himadri; Ramesh, Kheerthana; Sahu, Rajendra Prasad; Saha, Anumeha; Sar, Pinaki; Kazy, Sufia Khannam (Frontiers in Microbiology, 2022)
Characterization of inorganic carbon (C) utilizing microorganisms from deep crystalline rocks is of major scientific interest owing to their crucial role in global carbon and other elemental cycles. In this study we investigate the microbial populations from the deep [up to 2908 meters below surface (mbs)] granitic rocks within the Koyna seismogenic zone, reactivated (enriched) under anaerobic, high temperature (50 °C), chemolithoautotrophic conditions. Subsurface rock samples from six different depths (1679 - 2908 mbs) are incubated (180 days) with CO2 (+H2) or HCO3- as the sole C source. Estimation of total protein, ATP, utilization of NO3 - and SO42- and 16S rRNA gene qPCR suggests considerable microbial growth within the chemolithotrophic conditions. We note a better response of rock hosted community towards CO2 (+H2) over HCO3-. 16S rRNA gene amplicon sequencing shows a depth-wide distribution of diverse chemolithotrophic (and a few fermentative) Bacteria and Archaea. Comamonas, Burkholderia-Caballeronia-Paraburkholderia, Ralstonia, Klebsiella, unclassified Burkholderiaceae and Enterobacteriaceae are reactivated as dominant organisms from the enrichments of the deeper rocks (2335 - 2908 mbs) with both CO2 and HCO3-. For the rock samples from shallower depths, organisms of varied taxa are enriched under CO2 (+H2) and HCO3-. Pseudomonas, Rhodanobacter, Methyloversatilis, and Thaumarchaeota are major CO2 (+H2) utilizers, while Nocardioides, Sphingomonas, Aeromonas, respond towards HCO3-. H2 oxidizing Cupriavidus, Hydrogenophilus, Hydrogenophaga, CO2 fixing Cyanobacteria Rhodobacter, Clostridium, Desulfovibrio and methanogenic archaea are also enriched. Enriched chemolithoautotrophic members show good correlation with CO2, CH4 and H2 concentrations of the native rock environments, while the organisms from upper horizons correlate more to NO3 -, SO42-, Fe and TIC levels of the rocks. Co-occurrence networks suggest close interaction between chemolithoautotrophic and chemoorganotrophic/fermentative organisms. Carbon fixing 3-HP and DC/HB cycles, hydrogen, sulfur oxidation, CH4 and acetate metabolisms are predicted in the enriched communities. Our study elucidates the presence of live, C and H2 utilizing Bacteria and Archaea in deep subsurface granitic rocks, which are enriched successfully. Significant impact of depth and geochemical controls on relative distribution of various chemolithotrophic species enriched and their C and H2 metabolism are highlighted.